The Role of Seniority-Based Succession (Ekberiyet) in Increasing Women’s Influence in The Ottoman Empire - Muhammad Luthfi Sartono; Fauzan Maulana Fattah (Indonesian Student Association Study Center in Türkiye, 2025)
This study discusses the transition of the succession system in the Ottoman Empire from a direct inheritance model from father to son to a seniority system, where the oldest male in the dynasty has the right to ascend the throne. This change had a significant impact on the increasing influence of women in the palace, especially Valide Sultan and Haseki Sultan. In this context, figures such as Kösem Sultan and Turhan Sultan used their positions to influence political policies and maintain the stability of power. This study uses a qualitative method with a historical and social approach, focusing on library research. By referring to historical sources, it was found that the transition of this succession system provided strategic advantages for women in the palace in strengthening their position in the power environment. Valide Sultan and Haseki Sultan obtained positions that allowed them to play an active role in government policy-making, both in the social, cultural, and economic fields.